Upaya Peningkatan Imunitas Tubuh melalui Edukasi Pangan dan Gizi bagi Pegawai dan Dosen di LLDIKTI Wilayah VIII: Efforts to Improve Body Immunity through Food and Nutrition Education for Employees and Lecturers in LLDIKTI Region VIII - I Gusti Ayu Wita Kusumawati; Ni Wayan Nursini; Ida Bagus Agung Yogeswara; Ni Putu Eny Sulistyadewi; Dylla Hanggaeni Dyah Puspaningrum; Ni Ketut Wiradnyani; Ida Bagus Ketut Mantra; Purwaningtyas Kusumaningsih; I Gede Mustika (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
The Covid 19 pandemic and unhealthy life style may lead to depression and anxiety followed by a decreasing of immune system. A healthy diet affects a person’s health and immune system. Objective: To provide education to the community, especially employees and lecturers in the LLDIKTI region VIII work environment, regarding food consumption and nutrition that can prevent stress and increase endurance during a pandemic. Methods: The activity begins with preparation, implementation and evaluation. Education is carried out using virtual media through zoom meetings, which are in the form of webinar series containing lectures and discussions. At the beginning of the activity, partners are given a pre-test and at the end of the discussion partners are given a post-test. Community service activities are carried out from October 13, 2021, to November 13, 2021. The evaluation was carried out using a knowledge questionnaire based on the material presented by the speaker. The results of the community service activities showed an increase in partner knowledge about food and nutrition consumption that can prevent stress and increase endurance during a pandemic. Suggestion: It is necessary to conduct training and assistance in hygiene food processing to produce processed innovations that can be used to increase body immunity.